Selection of Nutmeg Mother Trees In The Germplasm Collection at Cicurug Experimental Station Sukabumi - Nurliani Bermawie; NFN Ma’mun; Susi Purwiyanti; Wawan Lukman (Pusat Penelitian dan Pengembangan Perkebunan, 2018)
Nutmeg has been known as native spices to Indonesia. The widespread cultivation of nutmeg cause the high demand for nutmeg seeds, hence the source of quality seeds is needed. The purpose of this study was to evaluate sex, morphological characters, yield and quality to be recommended as source of quality seeds. The research was conducted at Cicurug Experimental Station, Sukabumi (550 m asl). The parameters observed were the sex of trees, and yield per tree harvested for nine years from 2007-2015. The quality was analyzed using Gas Chromatography Mass Spectra (GC-MS). The sex of the trees observations resulted 152 accessions (34.7 %) were pure males, 83 accessions (18.9 %) bisexual males and 203 accessions (46 %) pure females. Based on fruit yield, from 203 female nutmeg trees, 20 accessions produced high fruit yield >2,500 fruits/tree/year. GC-MS analysis showed the number of identified compounds were 18-30 compounds with the main components were α-pinene, ß-pinene, sabinene, limonene, 4-terpineol, safrol, elemicin and myristicin. The 20 selected accessions met the quality standards for the essential oil, limonene and elemicin levels, but only five accessionsmet the standard quality for α-pinene, two accessions for ß-pinene, five accessions for sabinen, 18 accessions for 4-terpineol, 13 on safrol, and 11 accessions for myristicin levels. Tree selected accessions Botol 122, Irian 112 and Kupal 139 fulfilled nine out of ten quality parameters, whereas other accessions only fulfilled eight to four quality parameters. Accessions that achieved the criteria of fruit production should be recommended as source of quality seeds.